ERROR ANALYSIS ON TRANSLATION TEXT IN SMA N 1 WALED STUDENTS - Lili Sururi Asipi; Ninik Hernika (Tomorrow's Education Journal, 2023)
This research was conducted based on the fact that most students still make many mistakes in conveying the meaning of Indonesian to English. Lack of vocabulary, facing ambiguity from Indonesian to English, words, phrases, and sentences. The ability to translate is a language skill that must be mastered. Foreign language learners must have the ability to translate both orally and in writing. Therefore, the purpose of this research is (1) to find out the types of mistakes made by students in translating Indonesian procedural text into Indonesian and (2) to find out the mistakes made by students in translating procedural texts. This study uses a qualitative method using a language error analysis approach. Data collection techniques were carried out by means of written documents obtained from 15 participants from SMA N 1 Waled. The results show that students make mistakes in terms of vocabulary, use of prepositions, and use of tenses. This shows that students’ understanding is still not sufficient in choosing the correct vocabulary and the appropriate grammar arrangement in translating Indonesian into English through procedure text.